1997
DOI: 10.1021/bi9612778
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Photophysics of a Primase-Derived Peptide Are Sensitive to the Peptide's Zinc-Bound State:  Proof That the Bacterial Primase Hypothetical Zinc Finger Sequence Binds Zinc

Abstract: A 35-amino acid peptide corresponding to the putative "zinc finger" sequence of primase was prepared to study its zinc binding properties. When zinc was added to the peptide, it was found that the fluorescence quantum yield of the single tyrosine increased by 46% and the average lifetime by 34%. The binding stoichiometry was one zinc per peptide. Below pH 6.0 and above pH 8.5, the zinc-peptide binding affinity was less than 1 microM and could be accurately determined. Interpolation from those binding constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
6
9
0
Order By: Relevance
“…This result is in accordance with the tetrahedral geometry described previously for the CCHC motif family [11,12]. Furthermore, in the UV region of the spectra, absorption bands at 313 and 352 nm appear, owing to a charge transfer from S V to Co# + , in accordance with published results on other peptides and proteins [29,30]. When performing spectroscopic studies at different pH values, we showed that metal co-ordination does not take place below pH 5.2, owing to histidine protonation.…”
Section: Characterization Of Peptide-metal Complexessupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in accordance with the tetrahedral geometry described previously for the CCHC motif family [11,12]. Furthermore, in the UV region of the spectra, absorption bands at 313 and 352 nm appear, owing to a charge transfer from S V to Co# + , in accordance with published results on other peptides and proteins [29,30]. When performing spectroscopic studies at different pH values, we showed that metal co-ordination does not take place below pH 5.2, owing to histidine protonation.…”
Section: Characterization Of Peptide-metal Complexessupporting
confidence: 92%
“…The Zn# + co-ordination with these peptides was estimated to be 10$-10%-fold stronger than Co# + co-ordination (with K Co d and K Zn d approx. 1 µM and 100 pM respectively) [11,29,30]. In the present study we performed a detailed investigation of the stability of the NC N-terminal cobalt-finger and zinc-finger by using UV-visible absorption spectroscopy and HPLC chromatography.…”
Section: Stability Studiesmentioning
confidence: 99%
“…This binding of DnaG/DnaB is critical for the recruitment of the primase to the replication fork. DnaG protein tightly binds one Zn, which is ligated by three cysteinyl sulfhydryls and one histidine nitrogen near the N terminus (72,73). Apoprimase, however, synthesizes primers in a sequence-specific manner, which eliminates a role for Zn in catalysis (73) and ascribes to it a structural one, possibly to prevent disulfide formation.…”
Section: The E Coli Replisome Protein Componentsmentioning
confidence: 99%
“…De novo designed metal binding motifs usually have tetra- or tri-peptide structures. Square planar or tetrahedral coordination environments can easily be achieved with tri- or tetra-peptide structures [ 25 , 26 ], providing a flexible and stable chelate ring for metal ions. Burrows et al prepared a CGH motif and characterized its coordination chemistry [ 27 ].…”
Section: Introductionmentioning
confidence: 99%